Konseling Diet Rendah Kolesterol Dan Tinggi Serat Terhadap Pengetahuan Dan Kadar Kolesterol Pada Penderita Hiperkolesterolemia - Bintang Siti Fadilah; Suparman Suparman; Mira Mutiyani; Dadang Rosmana; Priska Natasya (Poltekkes Kemenkes Bandung, 2019)
Consumption pattern changes cause people to consume foods that contain high fat and cholesterol. It will result in hypercholesterolemia. According to WHO in 2011 it is estimated that around 35% of Indonesians have higher cholesterol levels than normal limits, meaning a third of Indonesia's population is at high risk of hypercholesterolemia. In addition, lack of knowledge about dietary settings becomes a poor impact as a risk of degenerative diseases. One effort to cope with this is nutritional counseling on low cholesterol and high fiber diets. The study aims to determine the effect of low cholesterol and high fiber diet counselling on knowledge and total cholesterol levels in patients with hypercholesterolemia. Data collection is conducted in February 2019 in the working area of Pasirkaliki Puskesmas using the design of experimental quasi research with one group Pretests posttest design. Samples were selected for purposive sampling and 12 people gained. Data was analyzed using T-Test and Wilcoxon paired test samples. The results showed there was the influence of low-cholesterol and high-fiber diet counselling on knowledge (P = 0,002) and decreased total cholesterol levels (P = 0,000). It is recommended that people with hypercholesterolemia still apply a low cholesterol and high fiber diet in an effort to control the increase in total blood cholesterol levels.